Reconceptualizing Legal Protection for Drug Addicts: A Restorative Justice Perspective in Indonesia - Diovanni Nurfuzi Sari Hendona; Ade Maman Suherman; Indra Yudha Koswara; Tri Setiady; Wiwin Triyunarti (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze legal protections for drug addicts and to examine the relevance of applying restorative justice within the Indonesian criminal justice system, particularly in recognizing addicts as legal subjects who possess a dual role as both perpetrators and victims. The methods employed are normative legal analysis using statutory, conceptual, and case-based approaches, analyzed qualitatively through primary legal sources, court rulings, and relevant academic literature. The novelty of this study lies in the development of an integrated analytical model that combines legal protection theory, victimology, and the principles of restorative and rehabilitative justice, while formulating a regulatory harmonization model that positions drug addicts as subjects of legal protection within narcotics policy. The findings indicate that the legal status of drug users within Indonesia’s criminal justice system remains ambiguous, leading to the dominance of a repressive approach that conflicts with the principle of rehabilitation. The normative inconsistency between Articles 54 and 103 and the criminalization provisions in Article 127 of Law No. 35 of 2009, as well as the disharmony with criminal procedure law and the internal policies of law enforcement agencies, creates legal uncertainty in practice. The conclusions of this study affirm that regulatory reform is needed, oriented toward strengthening rehabilitation as a right of drug users, strengthening rehabilitation institutions, reducing social stigma, and optimizing restorative justice approaches to realize a criminal justice system that is more just, humane, and sustainable.